The effectiveness of Polya’s problem-solving strategy in enhancing mathematical word problem comprehension among fifth-grade students - Evi Fitriani (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
Despite its importance, students' difficulty in comprehending and solving mathematical word problems persists in elementary education. This quasi-experimental study examines the effectiveness of Polya’s four-step problem-solving strategy in improving this competency. Fifth-grade students (N=45) from SD Negeri 7 Buntok were assigned to an experimental group (taught using Polya’s strategy) and a control group (conventional instruction). A pretest-posttest design with a mathematical word problem test, scored via an analytic rubric, measured competency in problem understanding, solution process, accuracy, and answer correctness. Results showed a significantly greater improvement in the experimental group (pretest M=58.2, posttest M=78.6) compared to the control group (pretest M=56.9, posttest M=65.3). Statistical analysis (independent samples t-test) confirmed a significant difference between the groups' posttest scores (p < 0.05). The findings demonstrate that explicitly teaching Polya's strategy significantly enhances students' systematic problem-solving skills and conceptual understanding of word problems. This study provides empirical evidence for integrating structured heuristic strategies into primary mathematics curricula to build foundational problem-solving proficiency.